The Borderlands of Belief: Phil Rickman's Merrily Watkins Mysteries - Schrock, Chad D. (Christianity & literature, 2018)
Merrily Watkins is a highly unconventional Anglican priest and exorcist, and her eponymous mystery series represents the church she serves as hopelessly out of touch culturally and morally. Such distance from conventional Christianity manifests a sensibility increasingly called postsecular: distaste for the power moves of organized religion alongside acknowledgement that the ongoing contemporary quest for and experience of transcendent meaning disproves triumphalist secularization. The series prioritizes Christianity within this anti-dogmatic religious landscape because of Christianity's stable systems of symbol and ritual and its cruciform ethics of humility and faithfulness uniquely appropriate to approach the most important mysteries in the world.